Strengthening Digital Learning for Archipelago Teachers in Letti Island: Pengabdian - Meyer, Fredi; Tiwery, Yulina; Sarah Kamanasa, Louisa; Sartin Tiwery, Dian; Saartje Ferdinandus, Marcy; F. J. Lekawael, Rosina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program titled "Strengthening Digital Learning for Archipelago Teachers in Letti Island" was carried out to empower English teachers in Letti Island with the knowledge and skills needed to integrate digital tools into their teaching practices. Letti Island, located in Southwest Maluku Regency, faces significant challenges in internet accessibility, impacting education quality and equity. The program involved a one-day workshop with presentations, practical digital training, group discussions, and collaborative activities. The results indicated that the experience motivated and enlightened all participating teachers. Despite infrastructural limitations, they expressed strong enthusiasm to apply what they had learned in their classrooms. This initiative highlights the importance of continuous professional development for educators in rural areas and suggests the need for greater government attention to improving access to digital resources. Future programs of this nature are encouraged to sustain and expand the positive impact on teaching and learning in remote island communities.